2021
DOI: 10.1007/s10877-021-00701-4
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of renal region, cerebral and peripheral oxygenation for predicting postoperative renal impairment after CABG

Abstract: Patients undergoing coronary artery bypass grafting (CABG) are at risk of developing postoperative renal impairment, amongst others caused by renal ischemia and hypoxia. Intra-operative monitoring of renal region tissue oxygenation (SrtO2) might be a useful tool to detect renal hypoxia and predict postoperative renal impairment. Therefore, the aim of this study was to assess the ability of intra-operative SrtO2 to predict postoperative renal impairment, defined as an increase of serum creatinine concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…AUC-ROC analysis for renal rSO 2 values < 55% for >1.5 min showed a sensitivity of 64.7% and a specificity of 88.5% (AUC = 0.777, 95% CI: 0.669–0.885; p < 0.001) for predicting CSA-AKI. Nonetheless, the usefulness of renal rSO 2 measurements in detecting CSA-AKI could not be confirmed in other investigations [ 65 , 66 ], and two studies even suggested that low renal rSO 2 values before and during CPB may have kidney-protective effects [ 47 , 66 ]. In a small prospective cohort study of 66 infants (≤10 kg) undergoing CHD repair with CPB, infants with lower baseline and i.o.…”
Section: Kidney Diseasesmentioning
confidence: 99%
“…AUC-ROC analysis for renal rSO 2 values < 55% for >1.5 min showed a sensitivity of 64.7% and a specificity of 88.5% (AUC = 0.777, 95% CI: 0.669–0.885; p < 0.001) for predicting CSA-AKI. Nonetheless, the usefulness of renal rSO 2 measurements in detecting CSA-AKI could not be confirmed in other investigations [ 65 , 66 ], and two studies even suggested that low renal rSO 2 values before and during CPB may have kidney-protective effects [ 47 , 66 ]. In a small prospective cohort study of 66 infants (≤10 kg) undergoing CHD repair with CPB, infants with lower baseline and i.o.…”
Section: Kidney Diseasesmentioning
confidence: 99%
“…The evidence regarding clinical utility in these circumstances is equivocal. [8][9][10] There are only limited reports of the use of NIRS during EVT, all including patients with an internal carotid artery (ICA) or middle cerebral artery (MCA) occlusion. [11][12][13][14] These studies show conflicting outcomes, which might be due to application of the NIRS 'sensor' (i.e.…”
Section: Near-infrared Spectroscopy Monitoring During Endovascular Tr...mentioning
confidence: 99%
“…Ten out of 20 patients were female, the mean ± SD age was 71 ± 16 years, and all patients had an M1 occlusion. The median (interquartile range [IQR]) NIHSS score at baseline was 15 [7][8][9][10][11][12][13][14][15][16][17][18][19][20], and most (14/20) patients had a moderate to good collateral status (Supplemental Tables 1 and 2).…”
Section: Descriptive Data Patient Demographics and Co-morbiditiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the evidence supporting its use in the adult population is limited. In patients undergoing cardiac surgery with cardiopulmonary bypass, renal tissue oxygen saturation had an acceptable agreement with renal vein saturation [7], but conflicting results were found regarding the association of renal region desaturation with postoperative renal injury [16,17]. One point of concern is that the penetration depth of the sensors might be insufficient to reach the kidney in adults.…”
Section: Introductionmentioning
confidence: 99%